The Scarlet Letter The Manga Edition - Hawthorne, Nathaniel; Sexton, Adam; Lin, Yali (Houghton Mifflin, 2013)
The Scarlet Letter: The Manga Edition will be a hit with both manga readers and in the classroom. A four-page essay at the beginning ties the novel and manga together; the rest of the book is taken up with the manga novel itself. So, there should be strong carryover between those people who are manga readers and those teachers/students who want a new and unique way to read the plays. Our The Scarlet Letter manga is true to the original context of the play--we don't take Hester and Pearl and set them in a setting/time that's not relevant to Hawthorne's original and intended time/setting. You could say that ours is "true" to the novel.
Adam Sexton is author of Master Class in Fiction Writing and editor of the anthologies Love Stories, Rap on Rap, and Desperately Seeking Madonna. He has written on art and entertainment for The New York Times and The Village Voice, and he has taught fiction writing and literature at New York University and Parsons School of Design. A graduate of Columbia University and the University of Pennsylvania, he lives in Brooklyn with his wife and son. Yali Lin is the artist of Shakespeare's Romeo and Juliet: Manga Edition. Since earning her BFA in cartooning from the School of Visual Arts in 2006, she has been teaching manga courses to children and teens in New York City. In her free time, she enjoys card making, organizing, and creating her own comics which you can find at www.yalilin.com. She would like to thank Nicolas Cinquegrani, Sophia Ma, and Ray Lin for their great help on this book.